2013
DOI: 10.1093/jnci/djt025
|View full text |Cite
|
Sign up to set email alerts
|

Regional Variation in Spending and Survival for Older Adults With Advanced Cancer

Abstract: There is substantial regional variation in Medicare spending for advanced cancer, yet no consistent association between mean regional spending and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
91
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(94 citation statements)
references
References 32 publications
1
91
0
Order By: Relevance
“…Clinicians face considerable uncertainty in choosing appropriate treatment approaches for patients with advanced cancer, and previous work has shown that there is substantial regional variation in per capita Medicare spending for this population. Furthermore, regional variation in advanced cancer spending was not associated with survival differences in elderly patients with advanced cancer,[8] supporting the conclusion that the marginal value of high-intensity practice patterns in the advanced cancer setting is low. Here, we examine regional variation in Medicare spending for elderly patients (ages sixty-five and older) with advanced cancer, with spending claims broken down into thirteen distinct cancer-relevant service categories.…”
mentioning
confidence: 71%
“…Clinicians face considerable uncertainty in choosing appropriate treatment approaches for patients with advanced cancer, and previous work has shown that there is substantial regional variation in per capita Medicare spending for this population. Furthermore, regional variation in advanced cancer spending was not associated with survival differences in elderly patients with advanced cancer,[8] supporting the conclusion that the marginal value of high-intensity practice patterns in the advanced cancer setting is low. Here, we examine regional variation in Medicare spending for elderly patients (ages sixty-five and older) with advanced cancer, with spending claims broken down into thirteen distinct cancer-relevant service categories.…”
mentioning
confidence: 71%
“…3 Despite advances in tumor profiling and drug development, improvements in health outcomes have been limited, and many new drugs are associated with both adverse effects and high costs. [19][20][21] Thus, for patients with metastatic cancer, the expected benefits of chemotherapy must be weighed against the possibility of treatment-related toxicities. 6,22 In our analysis of a population-based cohort of older adults with advanced cancer, chemotherapy was associated with increased risk of hospitalization, and a considerable proportion of admissions were attributable to likely chemotherapy-related toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Other research has demonstrated variation in the use of inpatient services for patients with advanced cancer at the regional level but not doi: 10 at the practice level. 9 Some pilot projects have reported reductions in inpatient utilization through enhanced care management. 10,11 Stakeholders have emphasized opportunities to produce savings by supporting poorly reimbursed aspects of care, such as care planning, care coordination, and enhanced outpatient services to prevent costly inpatient admissions.…”
mentioning
confidence: 99%